Lesson preparation for inclusive teaching of learners with disabilities from grade 1 to 7 at Kankumba Primary School - Lawrence Nsofwa Malata; Kenneth Kapalu Muzata (International Journal of Educational Innovation and Research, 2022)
The inclusive approach calls for schools to make appropriate curriculum changes to the learning so that each classroom is able to address the learning needs of all children, including those with disabilities. Inclusive education requires good lesson preparation by teachers and involves putting in order all relevant materials considering the concepts of adaptation, accommodation and modification. It appears that the aspect of inclusive lesson preparation for learners with disabilities has not been taken seriously and this could be the major contributing factor to poor performance. However, this article will explore lesson preparation for inclusive teaching of learners with disabilities from grade 1 to 7 at Kankumba primary school in Rufunsa district, Zambia. The study adopted a case study design and it employed a qualitative approach to collect data. The participants were purposively selected and the sample comprised 18 participants that were categorized as follows: Headteacher (1), Parents (5), Class Teachers (6), and children with disabilities (6). The major findings of the study revealed that teachers did not prepare lessons inclusively. Some indicators of lack of inclusive planning were the absence of inclusive methods in lesson plans, whereby teachers only planned group work and lecture methods without indicating how the learners with disabilities would benefit. The selection of teaching and learning aids did not depict inclusion for learners with disabilities. The study further revealed that the lack of proper inclusive lesson delivery and inclusive lesson preparation was exacerbated by a lack of knowledge on inclusive lesson preparation by teachers. It was recommended that in-service teachers need capacity building in inclusive lesson preparation and a further review of how inclusive lesson preparation can be intensified in the teacher education curriculum.